Production of charmed pseudoscalar mesons in antiproton-proton annihilation - Haidenbauer, J.; Krein, G. [UNESP] (American Physical Society (APS), 2014)
We study the production of charmed mesons (D, Ds) in antiproton-proton (p̄p) annihilation close to the reaction thresholds. The elementary charm production process is described by baryon exchange and in the constituent quark model. Effects of the interactions in the initial and final states are taken into account rigorously. The calculations are performed in close analogy to our earlier study on p̄p→K̄K by connecting the processes via SU(4) flavor symmetry. Our predictions for the DD̄ production cross section are in the order of 10-2-10-1μb. They turned out to be comparable to those obtained in other studies. The cross section for a Ds+Ds- pair is found to be of the same order of magnitude despite the fact that its production in p̄p scattering requires a two-step process. © 2014 American Physical Society.